Effect of Beta-blockers on Extracranial Arteriovenous Malformations - Sarah Chastanet; Annabel Maruani; Boris Laure; Denis Herbreteau; Aline Joly (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)